(untitled) (Hong Kong Journal of Ophthalmology, 2001)
Purpose: To evaluate the correlation between mitral valve prolapse and permanent or temporary visual loss in young patients. Materials and methods: Thirty two patients (age range, 16 to 41 years) with permanent or temporary visual loss were included in this study. Eye examination, including fluorescein angiography, and general medical examination, including echocardiography, were performed. Results: Eight patients had central vein occlusion, 15 had branch retinal vein occlusion, and no pathology was found for 9. Seven patients showed mitral valve prolapse on echocardiography. Conclusion: Mitral valve prolapse is thought to be one of the most important reason for the clinical appearance of permanent or temporary (amaurosis fugax) visual loss in young patients.